The Dao of three-way decision and three-world thinking - Yao, Yiyu (International journal of approximate reasoning, 2023)
Three-way decision is about thinking, problem-solving, and computing in threes or through triads. Its philosophy and practice of triadic thinking appear everywhere. In particular, there are a number of three-world or triworld models in different fields and disciplines, where a complex system, a complicated issue, or an intricate concept is explained and understood in terms of three interrelated worlds, with each world enclosing a group of elements or representing a particular view. This paper examines various triadic metaphors and structures in general and three-world metaphors and conceptions in particular for building and explaining basic concepts of three-way decision. The three major objectives are (a) to formulate a TAO (Triading-Acting-Optimizing) framework of three-way decision, (b) to discuss the Dao, the Way of three-way decision, and (c) to articulate the Dao, the Way of three-world thinking. Three-world conceptions offer more insights into three-way decision with new viewpoints, methods, and modes. An emphasis of the paper is on the philosophy and the power of three-way decision for building high-level conceptual models. By using three-part structures, by focusing on only three things, or by considering three basic ingredients, we may build a theory, a model, or a method that is simple-to-understand, easy-to-remember, and practical-to-use.